Analysis of the Use of GERATIF (Interactive Numeracy Game) on the Numeracy Skills of Children Aged 5–6 Years - Vina Salsabilah Himawati; Nur Ika Sari Rakhmawati; Rachma Hasibuan; Sri Widayati; Dwi Jayanti Kurnia Dewi (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study was motivated by the problem of low numeracy skills among children aged 5–6 years, which is frequently encountered in early childhood education settings. This condition is influenced by learning activities that are insufficiently engaging and fail to motivate children. Meanwhile, technological advancements require the education sector to integrate digital media into the learning process. This study aimed to determine the effect of using GERATIF (Interactive Numeracy Game) on the numeracy skills of children aged 5–6 years. The study employed a quantitative approach using a quasi-experimental method with a nonequivalent control group design. The participants consisted of 40 children, comprising 20 children in the experimental group and 20 children in the control group. Data were collected through observation and documentation. The data obtained from both the experimental and control groups were analyzed using the Independent Samples t-Test. The results of the analysis indicated an Equal Variances Assumed significance value (Sig. 2-tailed) of 0.025. Since the significance value was less than 0.05, the alternative hypothesis (Ha) was accepted and the null hypothesis (H₀) was rejected. These findings demonstrate that the use of GERATIF (Interactive Numeracy Game) has a significant effect on the numeracy skills of children aged 5–6 years.